A review of post-nuclear-catastrophe management. (11th June 2015) - Nifenecker, Hervé
Abstract: The purpose of this paper is to make radioactive risk more generally understandable. To that end, we compare it to smoking tobacco. Further, we show that the concept of loss of life expectancy permits a quantitative comparison between various aggressions. The demystification of radioactive risk should lead to basic changes in post-catastrophe management, allowing victims to choose whether or not to leave contaminated areas. A less emotional appreciation of radioactive risks should lead to the adaptation of legal practices when dealing with probabilistic situations.